Elites or masses? A structural model of policy divergence, voter sorting and apparent polarization in U.S. presidential elections, 1972-2008 - Stefan Krasa; Mattias Polborn (Center for Economic Studies and ifo Institute (CESifo), 2012)
One of the most widely discussed phenomena in American politics today is the perceived increasing partisan divide that splits the U.S. electorate. A central contested question is whether this diagnosis is actually true, and if so, what is the underlying cause. We develop a model that relates the parties' positions on economic and cultural issues, the voters' ideal positions and the electorate's voting behavior, and apply the model to U.S. presidential elections between 1972 and 2008. The model allows us to recover candidates' positions from voter behavior; to decompose changes in the overall political polarization of the electorate into changes in the distribution of voter ideal positions and consequences of elite polarization; and to determine the characteristics of voters who changed their party allegiance.
Keywords: D72; 330; polarization; differentiated candidates; policy divergence; ideology; voter migration; Parteipolitik; Ideologie; Elite; Wahlverhalten; Schätzung; USA